2012
DOI: 10.1371/journal.pone.0035921
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mature MicroRNA Levels in Association with Dicer Loss in Human Temporal Lobe Epilepsy with Hippocampal Sclerosis

Abstract: Hippocampal sclerosis (HS) is a common pathological finding in patients with temporal lobe epilepsy (TLE) and is associated with altered expression of genes controlling neuronal excitability, glial function, neuroinflammation and cell death. MicroRNAs (miRNAs), a class of small non-coding RNAs, function as post-transcriptional regulators of gene expression and are critical for normal brain development and function. Production of mature miRNAs requires Dicer, an RNAase III, loss of which has been shown to cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 55 publications
8
89
4
4
Order By: Relevance
“…DROSHA is a double-stranded RNA-specific endoribonuclease that influences the initial step of miRNA biogenesis [43], the loss of which causes neuronal and glial abnormality, seizures, and neurodegenerative disorders [44]. McKiernan and colleagues found that reduced ribonuclease III levels in TLE patients might influence the epileptic phenotype [45]. Our study indicated that circ-EFCAB2 and circ-DROSHA might be involved in the process of TLE by regulating EFCAB2 and DROSHA (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…DROSHA is a double-stranded RNA-specific endoribonuclease that influences the initial step of miRNA biogenesis [43], the loss of which causes neuronal and glial abnormality, seizures, and neurodegenerative disorders [44]. McKiernan and colleagues found that reduced ribonuclease III levels in TLE patients might influence the epileptic phenotype [45]. Our study indicated that circ-EFCAB2 and circ-DROSHA might be involved in the process of TLE by regulating EFCAB2 and DROSHA (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Selective reduction in Dicer levels in tissue from TLE patients with severe hippocampal sclerosis (HS), suggested that Dicer loss may contribute to the pathogenesis of TLE-HS [26]. MiR-184 has been identified as a seizure-regulated miRNA and its inhibition increases neuronal death after seizures [27].…”
Section: Discussionmentioning
confidence: 99%
“…Profiling studies were recently reported using resected hippocampus from temporal lobe epilepsy (TLE) patients [29•-30] along with work on individual miRNAs in human epilepsy 22-26••]. Significant changes were found for just under 100 different miRNAs and a number of the same miRNAs changed expression in the same direction as in the experimental work.…”
Section: Introductionmentioning
confidence: 99%